Madness and Feminism: An Analysis of Women's Struggles in Bronte's Jane Eyre and Kaysen's Girl, Interrupted - Poshya Salar Abdulla; Atta Abdalwahid Ahmed (Engiscience Publisher, 2023)
This paper explores the representation of mad women in literature through the lens of psychoanalytical feminism. It focuses on analyzing the decades-old patterns of female objectification through the male gaze, and their being ruled as 'mad' or 'psychotic' for demanding equal rights as men. Through the use of psychoanalytic feminism theory, the paper studies the literary works of the late 1800s and early 1900s. And in relation to the birth of the feminist movement; it demonstrates how within the literature of that period, more often than not women were depicted as mentally ill and condemned to mental hospitals and psychotic institutions in order to receive extremely harsh treatments for illnesses that they do not have. The analysis will be performed on two literary works, that have been selected and seen as fitting for the topic, and they are: Jane Eyre by Charlotte Bronte, and Girl, Interrupted by Susanna Kaysen. With the leading characters of these two novels being female, and extracted from society for being ill-fitting, they become the perfect examples for describing the main points of this paper.